2018
DOI: 10.3389/fphys.2018.01139
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Contribution of Wildland Firefighters’ Personal Protective Equipment on Physiological Strain

Abstract: Activities performed by wildland firefighters are carried out wearing a personal protective equipment (PPE). Although the PPE protects workers from a wide variety of hazards, it may increase their physiological response and limit their performance. The aim of this study was to analyze the effect of the protective clothing (PPC) and the rest of the PPE elements (i.e., helmet, neck shroud, gloves, goggles, and mid-calf leather boots) on the wildland firefighters’ thermophysiological response during a moderate-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 57 publications
1
35
0
1
Order By: Relevance
“…Besides, fR can be used as an indicator of thermal stress because it is substantially influenced by body temperature [21]. This is important for workers operating in hot environments as well as for those wearing protective clothing and equipment that may interfere with thermoregulation, including firefighters [22].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, fR can be used as an indicator of thermal stress because it is substantially influenced by body temperature [21]. This is important for workers operating in hot environments as well as for those wearing protective clothing and equipment that may interfere with thermoregulation, including firefighters [22].…”
Section: Introductionmentioning
confidence: 99%
“…In heat stressed conditions, PPE can dramatically reduce their performance by reducing heat transfer and sweat evaporation . This is exemplified in the work undertaken by Carballo‐Leyenda et al They found that PPE led to a low perspiration evaporation rate, which increased the thermophysiological response of wildland firefighters and reduced performance by around 50% …”
Section: Limitations Of Currently Used Personal Protective Equipment mentioning
confidence: 94%
“…Specifically, it is common to perform the PT dressed in sports clothing (e.g., shorts, T-shirt, running shoes). However, wildland firefighters (WFF) have to wear their personal protective equipment (PPE) (i.e., coveralls, gloves, helmet and boots) during their deployments [ 9 , 10 ]. This fact might affect PT performance since wearing a protective ensemble is heavier (~6 kg) and more restrictive to heat dissipation than exercise clothing [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%